UMPool: A Carpooling System - Lee, Lye Eng (2023)
UMPool: A Carpooling System is a web-based system that brings benefits to carpool drivers, passengers, environment, and society. UMPool provides advance bookings for carpool services on our campus. This system enables users to manage profiles, carpool, verify drivers, review their carpool, and make payment. The demand of carpooling in the campus is increasing due to these major factors, vast campus area and limited public transport. Therefore, the objective of this proposed system is to study the existing system of carpooling, develop a web-based carpooling system for UMP and evaluate the effectiveness and functionality of the proposed system. This paper proposes functional and User Acceptance Testing (UAT) for the UMPool application. A total of 27 test cases were conducted to verify their performance, and UMPool achieved a 96.30% error-free rating with only one minor defect identified. From the results of UAT testing, the majority of participants agreed that the UMPool was effective in assisting them with carpooling. In conclusion, UMPool has successfully met all functional requirements and managed to overcome the case study's problem statement.